20.2 CANNABINOID 1 RECEPTOR AVAILABILITY AND MEMORY FUNCTION IN FIRST EPISODE PSYCHOSIS: A MULTI-MODAL PET AND FUNCTIONAL MRI IMAGING STUDY. (9th April 2019) - Borgan, Faith; Laurikainen, Heikke; Hietala, Jarmo; Howes, Oliver
Abstract: Background: The neurobiology of memory deficits in psychosis remains poorly understood and unaddressed by current treatments. The cannabinoid 1 receptor (CB1R) modulates memory, and cannabinoids drugs can both induce psychotic symptoms and impair memory encoding. In view of this, we investigated memory and CB1R availability in first episode psychosis (FEP). Methods: Sixty-eight volunteers (33 FEP and 35 controls) completed the Sternberg working memory paradigm during an fMRI scan. A subset of these volunteers (20 FEP and 20 controls) underwent a [11C]MePPEP PET scan to measure CB1 receptor availability in vivo using a full arterial input function. The patients were antipsychotic naïve/ free. Results: There was a significant main effect of group on CB1R availability (F(3, 40)=4.123, p<0.05), with moderate to large effect size reductions in the patient group in the hippocampus, (Hedge's g=0.85), anterior cingulate (ACC) (Hedge's g=0.81) and orbitofrontal cortex (OFC) (Hedge's g=0.67). Volunteers showed significantly greater BOLD signal in the anterior cingulate cortex during encoding as working memory load demands increased (Pcorrected<0.05), consistent with the role of this region in encoding. Relative to healthy volunteers, first episode psychosis patients showed significantly greater functional activation in the anterior cingulate cortex during memory encoding (MNI coordinates: x=-8, y=44, z=0); T=4.36, Z=3.88, pcorrected=0.013; voxel size=92). Mean fMRI activation during encoding positively correlated with CB1R availability in the anterior cingulate (R=0.509, p<0.05). Conclusions: We show for the first time as far as we are aware in untreated first episode patients that CB1R availability is reduced, and that this is linked to altered cortical activation during memory encoding in patients. These findings are consistent with evidence that CB1R regulate synaptic transmission and plasticity involved in memory and identify the CB1R as a potential therapeutic target.